Acurácia do teste de escada utilizando o consumo máximo de oxigênio como padrão-ouro - Cataneo, Daniele Cristina [UNESP]; Cataneo, Antonio José Maria [UNESP] (FapUNIFESP (SciELO), 2007)
Objective: To determine the accuracy of the variables related to the fixed-height stair-climbing test (SCT) using maximal oxygen uptake (V̇O 2 max) as the gold standard. Methods: The SCT was performed on a staircase consisting of 6 flights (72 steps; 12.16 m total height), with verbal encouragement, in 51 patients. Stair-climbing time was measured, the variables 'work' and 'power' also being calculated. The V̇O2 max was measured using ergospirometry according to the Balke protocol. We calculated the Pearson linear correlation (r), as well as the values of p, between the SCT variables and V̇O2 max. To determine accuracy, the V̇O 2 max cut-off point was set at 25 mL/kg/min, and individuals were classified as normal or altered. The cut-off points for the SCT variables were determined using the receiver operating characteristic curve. The Kappa statistic (k) was used in order to assess concordance. Results: The following values were obtained for the variable 'time': cut-off point = 40 s; mean = 41 ± 15.5 s; r = -0.707; p < 0.005; specificity = 89%; sensibility = 83%; accuracy = 86%; and k = 0.724. For 'power', the values obtained were as follows: cut-off point = 200 w; mean = 222.3 ± 95.2 w; r = 0.515; p < 0.005; specificity = 67%; sensibility= 75%; accuracy = 71%; and k = 0.414. Since the correlation between the variable 'work' and V̇O2 max was not significant, that variable was discarded. Conclusion: Of the SCT variables tested, using V̇O2 max as the gold standard, the variable 'time' was the most accurate.
Accuracy of the stair-climbing test using maximal oxygen uptake as the gold standard
Keywords: Ergometry; Exercise test; Heart function tests; Respiratory function tests; Spirometry; adolescent; adult; aged; epidemiology; ergometry; exercise test; female; human; male; methodology; middle aged; motivation; motor activity; oxygen consumption; physiology; spirometry; standard; time; Adolescent; Adult; Aged; Epidemiologic Methods; Exercise Test; Female; Humans; Male; Middle Aged; Motivation; Motor Activity; Oxygen Consumption; Time Factors